The Phenomenology of Embodied Subjectivity
XXXIX, 356 p.
Keywords: The 17 original essays of this volume explore the relevance of the phenomenological approach to contemporary debates concerning the role of embodiment in our cognitive, emotional and practical life. The papers demonstrate the theoretical vitality and critical potential of the phenomenological tradition both through critically engagement with other disciplines (medical anthropology, psychoanalysis, psychiatry, the cognitive sciences) and through the articulation of novel interpretations of classical works in the tradition, in particular the works of Edmund Husserl, Maurice Merleau-Ponty and Jean-Paul Sartre. The concrete phenomena analyzed in this book include: chronic pain, anorexia, melancholia and depression.